PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI SIERRRA LEONE TAHUN 2009-2011 - Rani Hariani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to describe the effectiveness of the World Food Programme (WFP) in addressing the food insecurity in Sierrra Leone. Sierra Leone is a country in West Africa which has the potential of natural resources. In 2009 the World Food Programme (WFP) establish a program to address the food crisis in Sierra Leone nature. Programs created aims to rehabilitate livelihoods and improve the nutrition of children and pregnant women in Sierra Leone.This study is a qualitative research with the study of literature. describe and explain the program of the World Food Programme (WFP), which is engaged in food aid. In this study, the authors use the analysis of the level of international organizations used theory is the theory of the role, perspective used in this study is the perspective of pluralism.This study addressed the World Food Programme (WFP) was able to reduce wishful crisis that occurred in sierra leone. Rebuilding livelihoods and reduce malnutrition of mothers and children through the mechanism of food-for-training, food-for-work, cash-for-work..Keywords: food insecurity, food-for-training, food-for-work, cash-for-work. WFP